Challenges and solutions for secure information centric networks: A case study of the NetInf architecture. (April 2015) - Loo, Jonathan; Aiash, Mahdi
Abstract: A large number of emerging Internet applications require information dissemination across different organizational boundaries, heterogeneous platforms, and a large, dynamic population of publishers and subscribers. A new information-centric network architecture called Network of Information (NetInf) has been developed in the context of the FP7 EU-funded 4WARD project. This architecture can significantly improve large scale information distribution. Furthermore, it supports future mobile networks in situations with intermittent and heterogeneous connectivity and connects the digital with the physical world to enable better user experience. However, NetInf is still in an early stage of implementation and its security is yet to be evaluated. The security concern of NetInf is a major factor for its wide-scale adoption. Therefore, this paper uses the X.805 security standard to analyse the security of the NetInf architecture. The analysis highlights the main source of threats and potential security services to tackle them. The paper also defines a threat model in the form of possible attacks against the NetInf architecture.